Cultural Awareness and the Implementation of a Sharia-Based Transactional System in Islamic Early Childhood Education - Anggi Sartika Rahman; Alfi Amalia (Al-Qalam Institue, 2026)
This study aims to examine the implementation of a Sharia-based transactional system, explore the level of cultural awareness supporting its implementation, and identify the factors influencing its effectiveness within an Islamic early childhood educational institution. A qualitative approach with a descriptive analytical design was employed. Four participants, consisting of a school leader, a financial administrator, a teacher, and a parent, were purposively selected. Data were collected through observations, in-depth interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing/verification. The findings reveal that the institution has consistently implemented Sharia economic principles in its financial transactions by emphasizing transparency, accountability, honesty, and amanah. High cultural awareness was evident through the internalization of Islamic values into organizational practices and daily institutional activities. The implementation was supported by strong Islamic educational values, leadership commitment, parental involvement, and a supportive socio-cultural environment, while challenges included limited technical expertise in Sharia financial management and the absence of comprehensive Sharia-based standard operating procedures. These findings imply that integrating Sharia financial governance with organizational culture can strengthen ethical governance, institutional accountability, and sustainable financial management in Islamic educational institutions.